Photocatalytic decolorization of methyl orange dye using SnO2-TiO2 nanocomposite particles synthesised by Ultrasonic Assisted Co-Precipitation Method - Azad , Md. Abdus Samad; Bahadur, Newaz Muhammed; Hossain, Md Shahadat; Masum, Abdullah Al (Recent Research in Science and Technology, 2023)
The ultrasonic-aided co-precipitation method was used to create SnO2-TiO2 nanocomposite particles. Scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), and UV-vis spectroscopy were used to characterize the nanocomposite particles. XRD patterns revealed the crystalline structure of particles and the average particle size determined by Debye Scherrer’s equation was found to be 11.355, 4.9577, and 4.333 nm for TiO2 nanoparticles, SnO2 nanoparticles, and SnO2-TiO2 nanocomposites, respectively. The Ti, Sn, and O species were confirmed to exist by energy-dispersive X-ray spectroscopy (EDS). The UV absorption peaks at 288, 305, and 350 nm were attributed to SnO2, TiO2-SnO2, and TiO2 respectively. The photocatalytic aspect was investigated in a model organic contaminant (methyl orange). Data obtained by the above-mentioned characterization methods confirmed the superior photocatalytic activity of SnO2-TiO2 nanostructure than SnO2 or TiO2 alone.